1959
DOI: 10.1111/j.1365-2672.1959.tb04619.x
|View full text |Cite
|
Sign up to set email alerts
|

The Value of the Association Escherichieae‐group D Streptococci in the Diagnosis of Contamination in Foods

Abstract: The tests for faecal contamination in foods, based on 'indicator species', should be reconsidered for the following reasons. First, in Europe, Eschekhio coli is regarded BB a specific index of such contamination; but, apparently through the use of antibiotics, the proportion of human faeces containing Klebaielka has risen from 5.2% in 1947 to 48.4% in 1956-7. Moreover, E. coli and other coli-aerogenes organisms may be absent from the gut of certain animals, notably the pig. Second, while the usual methods of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

1960
1960
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…This bacterium can be readily isolated, often in considerable numbers, from various foods of animal origin, including beef (Ayres, 1960;Jay, 1967), pork (Blickstad and Molin, 1983;Enfors et al, 1979;Myers et al, 1982), raw milk (Kielwein et al, 1969;Kleeberger, 1975), and poultry (Nagel et al, 1960), as well as fish (Molin and Stenstrom, 1984;Boulander et al, 1977), crabs (Faghri et al, 1984), and water (LeChevallier et al, 1980(LeChevallier et al, , 1982Biamon and Hazen, 1983;Rippey and Cabelli, 1979). In contrast to much of the literature in which this organism is considered an undesirable part of the microflora of a food, Buttiaux (1959) has reported that Aeromonas plays an important role in the biological processes involved in the manufacture of a French raw sausage ('saucisson cru'). The presence of A. hydrophila in a food at spoilage suggests that the organism is capable of competitive growth at refrigeration temperatures (5°C).…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium can be readily isolated, often in considerable numbers, from various foods of animal origin, including beef (Ayres, 1960;Jay, 1967), pork (Blickstad and Molin, 1983;Enfors et al, 1979;Myers et al, 1982), raw milk (Kielwein et al, 1969;Kleeberger, 1975), and poultry (Nagel et al, 1960), as well as fish (Molin and Stenstrom, 1984;Boulander et al, 1977), crabs (Faghri et al, 1984), and water (LeChevallier et al, 1980(LeChevallier et al, , 1982Biamon and Hazen, 1983;Rippey and Cabelli, 1979). In contrast to much of the literature in which this organism is considered an undesirable part of the microflora of a food, Buttiaux (1959) has reported that Aeromonas plays an important role in the biological processes involved in the manufacture of a French raw sausage ('saucisson cru'). The presence of A. hydrophila in a food at spoilage suggests that the organism is capable of competitive growth at refrigeration temperatures (5°C).…”
Section: Introductionmentioning
confidence: 99%
“…The greater resistance shown by these organisms, as compared with E. coli and other coliforms, to heating and freezing processes and to frozen storage has been cited as strong evidence supporting their use for this purpose (Larkin et al, 1955(Larkin et al, , 1956Kereluk and Gunderson, 1959b). Moreover, some doubt has been cast recently on the value of E. coli as an index of fecal pollution by the observations of Buttiaux (1959) and Young et al (1960) concerning the low recoveries of this organism from human feces. The enterococci appear to provide a good general index of fecal contamination and Streptococcus faecalis is believed to be a specific index of humaii pollution (Cooper and Ramadan, 1955;Barnes, Ingram, and Ingram, 1956), though findings quoted by Buttiaux (1958) cast some doubt on this conclusion.…”
mentioning
confidence: 99%
“…Da un esame della letteratura, Battiaux concluse che il 100% dei campioni di feci umane e suine conteneva enterococchi, mentre solo l'86-89% conteneva coliformi 10 . E. faecium fu riconosciuto nel 1899 e ulteriormente caratterizzato nel 1919 da Orla-Jensen 64 .…”
Section: Quadro Storicounclassified